(untitled) (Journal of Partial Differential Equations, 2017)
In this paper, we consider the viscous incompressible magnetohydrodynamic (MHD) system with a new boundary condition for a general smooth domain in R3. We obtain the well-posedness of the system and the vanishing viscosity limit result.